Evaluation of chloroquine therapy for vivax and falciparum malaria in southern Sumatra, western Indonesia - Sutanto, Inge; Endawati, Dedeh; Ling, Liem Hui; Laihad, Ferdinand; Setiabudy, Rianto; Baird, J Kevin (Malaria journal, 2010)
Chloroquine was used as first-line treatment for Plasmodium falciparum or Plasmodium vivax in Indonesia before the initial launch of artemisinin combination therapy in 2004. A study to evaluate efficacies of chloroquine against P. falciparum and P. vivax was undertaken at Lampung in southern Sumatra, western Indonesia in 2002. Patients infected by P. falciparum or P. vivax were treated with 25 mg/kg chloroquine base in three daily doses over 48 hr. Finger prick blood was collected on Days 0, 2, 3, 7, 14, 21 and 28 after starting drug administration. Whole blood chloroquine and its desethyl metabolite were measured on Days-0, -3 and -28, or on the day of recurrent parasitaemia. 42 patients infected by P. falciparum were enrolled, and 38 fullfilled criteria for per protocol analysis. Only six of 38 (16%) showed a response consistent with senstivity to chloroquine. 25 of 32 failures were confirmed resistant by demonstrating chloroquine levels on day of recurrence exceeding the minimally effective concentration (200 ng/mL whole blood). The 28-day cumulative incidence of resistance in P. falciparum was 68% (95% CI: 0.5260 - 0.8306). Thirty one patients infected by P. vivax were enrolled, and 23 were evaluable for per protocol analysis. 15 out of 23 (65%) subjects had persistent or recurrent parasitaemia. Measurement of chloroquine levels confirmed all treatment failures prior to Day-15 as resistant. Beyond Day-15, 4 of 7 recurrences also had drug levels above 100 ng/mL and were classified as resistant. The 28-day cumulative incidence of chloroquine resistance in P. vivax was 43% (95% CI: 0.2715 - 0.6384). These findings confirm persistantly high levels of resistance to chloroquine by P. falciparum in southern Sumatra, and suggest that high-grade and frequent resistance to chloroquine by P. vivax may be spreading westward in the Indonesia archipelago.